Goal directed therapy: how long can we wait? - Gordon, Anthony C (BioMed Central, 2005)
Intensive monitoring and aggressive management of perioperative haemodynamics (goal directed therapy) have repeatedly been reported to reduce the significant morbidity and mortality associated with high risk surgery. It may not matter what particular monitor is used to assess cardiac output but it is essential to ensure adequate oxygen delivery. If this management cannot begin preoperatively, it is still worth beginning goal directed therapy in the immediate postoperative period.